2019
DOI: 10.1002/jia2.25274
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among ART‐experienced people with HIV in South Africa

Abstract: Introduction People with HIV ( PWH ) are at increased risk for atherosclerotic cardiovascular disease ( CVD ). Screening for CVD risk factors is recommended but not routine in South African HIV clinics. We sought to describe the prevalence of CVD risk factors among antiretroviral treatment ( ART )‐experienced pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The proportion of male participants in the included studies was reported in all studies and it ranged from 21.4% to 60.9%. 29–48 Of the included studies, 11 30–32 34 35 39–43 46 reported on diabetes, five 36 38 44 47 48 reported on HIV, two 29 45 reported on stroke and one each reported on chronic kidney disease 33 and atrial fibrillation. 37 None of the included studies reported on obesity, dyslipidaemia, coronary heart disease, heart failure, peripheral heart disease and depression.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of male participants in the included studies was reported in all studies and it ranged from 21.4% to 60.9%. 29–48 Of the included studies, 11 30–32 34 35 39–43 46 reported on diabetes, five 36 38 44 47 48 reported on HIV, two 29 45 reported on stroke and one each reported on chronic kidney disease 33 and atrial fibrillation. 37 None of the included studies reported on obesity, dyslipidaemia, coronary heart disease, heart failure, peripheral heart disease and depression.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies to achieve even a modest lowering of the levels of BP in this group of persons are therefore important public health goals. [ 15 ] This study aimed to assess the prevalence of the key behavioral risk factors associated with high BP among people living with HIV, their awareness of and attitudes toward these factors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis and systematic review reported that the crude rate of CVDs in PLHIV was 61.8 per 10,000 person-years, suggesting that PLHIV were twice as likely to develop CVDs within sub-Saharan Africa, presenting the most disability-adjusted life year (DALY) loss of 0.87 million [8]. The prevalence of cardiovascular risk factors in HIV continues to rise creating a major public health concern in South Africa [9].…”
Section: Introductionmentioning
confidence: 99%